1998
DOI: 10.1038/sj.cdd.4400392
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin effects on F-actin and matrix proteins precede renal tubular cell detachment and apoptosis in vitro

Abstract: In primary cultures of porcine proximal tubular kidney cells and LLC-PK1 cells cisplatin (5 ± 50 mM) caused apoptosis and cell detachment; in both systems cell detachment occurred, preceded by a loss of cytoskeletal F-actin stress fibers within 4 ± 6 h, and a reduction of mRNA encoding for fibronectin, collagen a 2 type (IV) and laminin B2 within 17 ± 41 h. Prevention of F-actin damage by phalloidin prevented nuclear fragmentation, suggesting a relation between F-actin damage and apoptosis. Overexpression of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 20 publications
4
72
0
Order By: Relevance
“…17 The resulting pattern at the reticular lamina reported in Burns and Corwin 17 is reminiscent of that reported here following cisplatin treatment (Figure 5c), consistent with cisplatin disrupting actin dynamics. [43][44][45] Our in vivo data show that phalangeal scars formed in aminoglycoside-treated cochleas are more actin-rich than those formed in cisplatin-treated cochleas (Figure 8), further suggesting that cisplatin impairs F-actin dynamics in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…17 The resulting pattern at the reticular lamina reported in Burns and Corwin 17 is reminiscent of that reported here following cisplatin treatment (Figure 5c), consistent with cisplatin disrupting actin dynamics. [43][44][45] Our in vivo data show that phalangeal scars formed in aminoglycoside-treated cochleas are more actin-rich than those formed in cisplatin-treated cochleas (Figure 8), further suggesting that cisplatin impairs F-actin dynamics in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrated that Cap is potent in protecting against free radical damage induced by CDDP. CDDP gener- ates active oxygen species such as superoxide anion and hydroxyl radical 28,29) and stimulates renal lipid peroxidation. 23,[30][31][32] The free radical scavengers SOD are reported to provide partial protection against CDDP-induced structural and functional alteration in rats.…”
Section: Discussionmentioning
confidence: 99%
“…We next analysed the e ects of several inhibitors of MRC complexes I ± IV on ROS generation using inhibitor concentrations equal to or higher than those reported by others to inhibit the respective complexes in other cell types (Kruidering et al, 1997). The MRC 3,6,9,12,15,18,21,24 h and induction of MPT was detected as above.…”
Section: E Ects Of Mrc Inhibitors and Uncoupler On 4hpr-induced Ros Gmentioning
confidence: 99%